Relationship Between Anxiety Levels and Sleep Quality Among Older Adults at the West Java Elderly Social Service Center - Tri Wahyuningsih; Desi Natalia; Supiyanto; Reini Astuti (STIKes Budi Luhur Cimahi, 2026)
Sleep disturbance and anxiety are common among older adults, but evidence from residents of social care institutions in West Java remains limited. This study examined the association between anxiety levels and sleep quality among older adults residing at the West Java Elderly Social Service Center. A cross-sectional correlational study was conducted among 62 residents drawn from a source population of 160. Anxiety was assessed using the Indonesian version of the Geriatric Anxiety Scale (GAS), and sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). The association was evaluated using the Fisher-Freeman-Halton exact test, with Cramer's V used as a measure of effect size. Moderate anxiety was observed in 67.7% of participants, while 82.3% had good sleep quality. Good sleep quality was reported by 100% of participants with mild anxiety and 95.2% of those with moderate anxiety. Poor sleep quality was reported by 77.8% of participants with severe anxiety and all participants with panic-level anxiety. Anxiety level was significantly associated with sleep quality (p = 0.001; Cramer's V = 0.786). Higher anxiety categories were associated with a greater frequency of poor sleep quality, although the cross-sectional design did not establish causality. These findings provide institution-specific evidence for gerontological nursing and support the integrated assessment of anxiety and sleep quality among older adults in residential care.